Student of UiTM Segamat Campus preferences study on the usage of Maxis billing and prepaid service / Azleen Aisyah Zainen, Noraniza Samsudin and Robiyatulmunawarah Md. Arif (Faculty of Business and Management, 2001)
Nowadays, in the era of modem technology people are prefer and comfortable to use cellular phone in their communication. One of the popular Telecommunication Companies that provide the prepaid and billing service is Maxis Communication Bhd. This company is said to become the fourth cellular Phone Company to offer prepaid service1. In Malaysia, it is expected to have about one million prepaid card cellular phone subscribers by the end of 20002. It can be approved on a recent survey conducted by Jamaludin Ibrahim as Chief Executive Officer from Maxis Communication Bhd that showed the strongest demand came from the 18 to 24 age group commonly referred to as the young and trendy generation.